2021
DOI: 10.1097/ico.0000000000002677
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of a Corneal Epithelial Cyst

Abstract: To describe a case of intracorneal epithelial cyst and present a surgical technique successfully used to treat this patient.Methods: This interventional case report presents a 4-year-old boy with a progressive intrastromal corneal opacity and decreased vision in his right eye. The patient had no previous history of trauma or ocular surgery. After clinical examination and corneal optical coherence tomography, a presumptive diagnosis of a developmental epithelial cyst was made, and surgery was indicated. Four ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…While previous studies have reported cases of corneal cysts, they have not specifically addressed their association with CRS. Furthermore, all reported cases of corneal stromal cysts have been treated surgically, regardless of the underlying cause [8][9][10]. The rationale behind the use of topical steroids is their potential effect on enhancing the pump function of the endothelium, which may cause shrinkage and hydration of the fluid within the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have reported cases of corneal cysts, they have not specifically addressed their association with CRS. Furthermore, all reported cases of corneal stromal cysts have been treated surgically, regardless of the underlying cause [8][9][10]. The rationale behind the use of topical steroids is their potential effect on enhancing the pump function of the endothelium, which may cause shrinkage and hydration of the fluid within the cyst.…”
Section: Discussionmentioning
confidence: 99%